Clonal structure of rapid-onset MDV-driven CD4+ lymphomas and responding CD8+ T cells. - William N Mwangi; Lorraine P Smith; Susan J Baigent; Richard K Beal; Venugopal Nair; Adrian L Smith (PLoS Pathogens)
Lymphoid oncogenesis is a life threatening complication associated with a number of persistent viral infections (e.g. EBV and HTLV-1 in humans). With many of these infections it is difficult to study their natural history and the dynamics of tumor formation. Marek's Disease Virus (MDV) is a prevalent α-herpesvirus of poultry, inducing CD4+ TCRαβ+ T cell tumors in susceptible hosts. The high penetrance and temporal predictability of tumor induction raises issues related to the clonal structure of these lymphomas. Similarly, the clonality of responding CD8 T cells that infiltrate the tumor sites is unknown. Using TCRβ repertoire analysis tools, we demonstrated that MDV driven CD4+ T cell tumors were dominated by one to three large clones within an oligoclonal framework of smaller clones of CD4+ T cells. Individual birds had multiple tumor sites, some the result of metastasis (i.e. shared dominant clones) and others derived from distinct clones of transformed cells. The smaller oligoclonal CD4+ cells may represent an anti-tumor response, although on one occasion a low frequency clone was transformed and expanded after culture. Metastatic tumor clones were detected in the blood early during infection and dominated the circulating T cell repertoire, leading to MDV associated immune suppression. We also demonstrated that the tumor-infiltrating CD8+ T cell response was dominated by large oligoclonal expansions containing both "public" and "private" CDR3 sequences. The frequency of CD8+ T cell CDR3 sequences suggests initial stimulation during the early phases of infection. Collectively, our results indicate that MDV driven tumors are dominated by a highly restricted number of CD4+ clones. Moreover, the responding CD8+ T cell infiltrate is oligoclonal indicating recognition of a limited number of MDV antigens. These studies improve our understanding of the biology of MDV, an important poultry pathogen and a natural infection model of virus-induced tumor formation.